The Role of Educational Technologies in the Effective Organization of Literature Classes (Journal of Pedagogical Inventions and Practices, 2022)
This article provides information from the teacher on the implementation of new educational technologies in the teaching process, what to do to enrich them with various district methods that activate the activities of students in the effective organization of literature lessons.